2023
DOI: 10.1111/odi.14486
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin induces odontoblastic differentiation of human‐derived pulp stem cells via EphB4‐Mediated MAPK signaling pathway

Abstract: ObjectivesHuman‐derived pulp stem cells play key roles during dentinogenesis. Erythropoietin is reportedly involved in osteoblastogenesis and facilitates bone formation. However, the mechanism is still unknown. This research was to study the potential of erythropoietin in enhancing odontoblastic differentiation of human‐derived pulp stem cells and to determine the underlying mechanism.MethodsThe human‐derived pulp stem cells were treated with erythropoietin, EphB4 inhibitor, and MAPK inhibitors, and the odonto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Gelatin sponge was also reported to be used in rat direct pulp capping models. [ 46 , 47 ] In our study, we applied METTL3 with GSs in VPT and found that the treatment promoted the tertiary dentin formation. Although the GS is bio-compatible, bio-degradable, and widely used in dental treatment, it has poorly x-ray resistance.…”
Section: Discussionmentioning
confidence: 79%
“…Gelatin sponge was also reported to be used in rat direct pulp capping models. [ 46 , 47 ] In our study, we applied METTL3 with GSs in VPT and found that the treatment promoted the tertiary dentin formation. Although the GS is bio-compatible, bio-degradable, and widely used in dental treatment, it has poorly x-ray resistance.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, our study was conducted with a limited number of time points, in accordance with previous literature [ 47 ], we selected 4 weeks for extraction. However, studies have shown that on the 7 d after capping [ 42 ], more continuous dentin regeneration was observed in a 12 weeks study [ 54 ]. Longer experimental days should be selected for further experiments so that the final effect of dentin formation and the metabolism of CNPs can be observed.…”
Section: Resultsmentioning
confidence: 99%
“…In MDPC-23 cells, ALP activity and osteogenic markers were reduced after blocking the p38-MAPK signaling pathway ( Tang and Saito, 2018 ). Inhibition of the MAPK pathway also reduces odontoblastic differentiation of hDPSCs ( Gu et al, 2022 ). Moreover, various factors function positively via the p38 MAPK pathway to promote odontoblastic differentiation as shown in Figure 2 and Table 1 .…”
Section: Molecular Mechanisms Regulating Odontoblastic Differentiationmentioning
confidence: 99%